Preliminary phytochemical analysis and evaluation of the antioxidant and anti-proliferative effects of Plinia peruviana leaves: an in vitro approach. Issue 5 (4th March 2021) - Graziela Moraes, Greice; Mazziero, Maiara; Lovatto, Marina; Dornelles, Rafaela Castro; Nogueira-Librelotto, Daniele Rubert; Reuter, Cézane Priscila; Ortolan, Silvio; da Silva, Chana de Medeiros; Manfron, Melânia Palermo
Abstract: Plinia peruviana (Poir.) Govaerts (Myrtaceae) occurs from Pará to Rio Grande do Sul states, Brazil. The leaf extract of this species was investigated. The total of polyphenols and flavonoid contents were determined by spectrophotometric techniques. Antioxidant activity by the oxygen radical absorbance capacity (ORAC) and anti-proliferative activity was tested against the MCF-7 and HeLa lines. The amount of polyphenols from the lyophilized extract was 944 ± 0.0856 mg GAE/g, moreover, total flavonoid content of the extract of 531.8 ± 0.0040 mg RE/g extract. This study performed the first pharmacological exploration of the leaves of P. peruviana . Our results demonstrated the antioxidant and anti-proliferative effects of this specie on MCF-7 and HeLa cell lines. This makes this specie an interesting medicinal plant for human epithelial cervical cancer and human breast cancer anti-proliferative approach. Abstract :